An approach to testing undiluted e-cigarette aerosol in vitro using 3D reconstituted human airway epithelium. (February 2019) - Bishop, E.; Haswell, L.; Adamson, J.; Costigan, S.; Thorne, D.; Gaca, M.
Abstract: The data presented here show that to provide an estimate of the relative cytotoxicity and therefore potency of e-cigarettes, undiluted aerosol techniques can be used. With the emergence of electronic nicotine delivery systems, fit-for-purpose in vitro screening methods are required. Reconstituted 3D human airway epithelium, was exposed to undiluted aerosols at the air-liquid interface, using a Vitrocell VC 10. TEER, cilia beat frequency and cytotoxic responses were assessed. Using two smoking regimes (ISO and HCI) a 3R4F reference cigarette, produced IC50 s of 5.2 and 2.1 min, 1458 ng/mL and 1640 ng/mL nicotine respectively. Using an open tank e-cigarette device, a full cytotoxicity dose-response curve was obtained giving an IC50 of 30 min with corresponding nicotine of 10, 957 ng/mL, 6–14 times less cytotoxic than cigarette smoke. A commonly used e-liquid flavourant cinnamaldehyde and known skin sensitizer was added to the standard e-liquid formulation and used as an aerosolised positive control, at 0.1, 0.025, 0.01 and 0%, demonstrating a full dose response. The delivery of undiluted aerosols in vitro has resulted in increased method sensitivity, throughput and quantitative e-cigarette comparisons. A positive control aerosol generated from a 'safe' e-liquid benchmark can inform risk assessments on supportable levels of flavour ingredients. Highlights: Undiluted aerosols were generated using a modified Vitrocell VC10. Dosimetry analysis showed that the VC10 was unaffected by modifications. Assay sensitivity increased to allow differences to e-cigarette aerosols to be measured. Cinnamaldehyde-spiked e-liquids were used as a positive aerosol control. The use of a 'safe' e-liquid as a benchmark for product risk assessment is introduced.